Antimicrobial activity of Malaysian honey against foodborne pathogen / Nabilah Mohd Nasir - Mohd Nasir, Nabilah (2016)
Emergence of food borne disease that increases year by year has become worrisome nowadays. It became troublesome at all developed, in developing and less developed country. Indeed, high mortality rate were recorded at less developing country every year. This problem become worst as the emergence of antibiotic resistance is in alert situation too. Meanwhile, therapeutic use of natural product including honey becomes awareness these days. The therapeutic use of honey has been use since ancient time. In Malaysia, various honeys have been found such as tualang, gelam, kelulut, acasia, hutan and pucuk daun honey. Among of these honey, tualang and gelam honey are known as their antioxidant, anti-inflammatory and antibacterial agent. However, there was limited study of these honeys against foodborne pathogen. Thus, this study is done to determine antimicrobial activity of tualang and gelam honey against foodborne pathogen which are S.aureus, E.coli and S.typhimurium. Antimicrobial Susceptibility Test (AST) is done to determine the antimicrobial activity of honey by disc diffusion assay. Concentration of honey at 80%, 60%, 40% and 20% were tested against those bacteria. Then, proceed with Minimum Inhibitory Concentration test by broth microdilution method. Two fold dilutions were prepared and producing 9 dilutions. Mueller Hinton broth is used as a medium and the test was performed triplicate to get a reliable result. Positive results of MIC were preceded with Minimum Bactericidal Concentration (MBC) by sub-culture on Mueller Hinton agar. The growth of organism was observed on the agar after 18 hours of incubation. The AST of this study showing all bacteria are resistance towards tualang and gelam honey. MIC test were precede and it show an inhibition of growth of tested bacteria. The MIC value of gelam honey is 37.5% while MIC value for tualang honey is 75.0% for all tested bacteria. MBC test result show gelam honey can kill bacteria at concentration of 37.5% for S.aureus and E.coli while for S.typhimurium at 75.0%. However, for tualang honey, it only shows MBC value for S.typhimurium at 75.0%. From the result, it can be seen gelam honey has better antimicrobial activity against tested bacteria than tualang honey. As a conclusion, gelam and tualang honey has antimicrobial activity against S.aureus, E.coli and S.typhimurium.